Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (Pcc) Cangkang Telur Itik Melalui Proses Hidrotermal Dengan Variasi Ph Dan Waktu Reaksi - Miftah Anugrah; Yelmida Azis; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (HAp, Ca10(PO4)6(OH)2) is one of the calcium phosphate compounds, which is the main inorganic component of human’s hard tissue such as bones and teeth. Hydroxyapatite (HAp) is a material used as an implant, adsorbent, and catalyst. The purpose of this study were to obtained product of hydroxyapatite from duck egg shell, studied the effect of variations in pH and reaction time on diameter of crystals and degree crystallinity of hydroxyapatite, and obtained the optimum conditions based on variations given. In this study, duck egg shell PCC and (NH4)2HPO4 were reacted using hydrothermal vessels with variations in pH of reactants at 8, 9, 10, 11, and 12, reaction time 15 and 16 hours, ratio of Ca/P 1,77 and HAp being synthesized at 140oC. The results were analyzed using X-Ray Diffractometer (XRD), Scanning Electron Microscopy (SEM-EDX), and Brunaeur-Emmet-Teller (BET). The result shows, the best hydroxyapatite were obtained at 15 hours of reaction time and pH 12 with diameter of crystals 26,91 nm, crystallinity 74,28%, ratio of Ca/P 1,60, and surface area 30,017 m²/g.Keywords: Hydroxyapatite, Hydrothermal, Crystallinity, PCC